Дослідження властивостей важкого кварконію методом Нікіфорова–Уварова для сильновзаємодіючої кварк-глюонної плазми при скінченній температурі - Rethika, K.T. (Publishing house "Academperiodika", 2025)
The N-dimensional radial Schr¨odinger equation with generalized two-body potential is solved, and the energy eigen values are calculated using the Nikiforov–Uvarov (NU) method in the N-dimensional space. The results are applied for the mass spectra of charmonium and bottomonium at finite temperature. The effect of dimensionality number on quarkonium mass is investigated. The dissociation temperature of different states of charmonium and bottomonium are calculated.